2004
DOI: 10.1590/s1519-69842004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and fertility of Macrobrachium amazonicum (Crustacea, Palaemonidae)

Abstract: In Brazil, studies with native freshwater prawn species were discontinued due to great importance of Macrobrachium rosenbergii. Therefore, it is necessary to continue investigations about our species, in order to develop technology adequate to our reality and in a future allow prawn farmers to culture other species. The aim of this study was to determine the fecundity and fertility of Macrobrachium amazonicum captured monthly from June 1999 to June 2001 from Jaguaribe River, Itaiçaba, Ceará, Brazil. Prawns wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
6
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 18 publications
8
38
6
7
Order By: Relevance
“…The number of eggs is highly variable in individuals of the same species, but increases in quantity with female size. Thus, a larger abdomen size implies in a greater accommodation of eggs in pleopods (Valenti, 1984;Silva et al, 2004). This positive correlation was observed in this study and in several others with M. amazonicum (Silva et al, 2004;Silva, 2006;Oliveira, 2010;Hayd & Anger, 2013;Meireles et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The number of eggs is highly variable in individuals of the same species, but increases in quantity with female size. Thus, a larger abdomen size implies in a greater accommodation of eggs in pleopods (Valenti, 1984;Silva et al, 2004). This positive correlation was observed in this study and in several others with M. amazonicum (Silva et al, 2004;Silva, 2006;Oliveira, 2010;Hayd & Anger, 2013;Meireles et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…However, Lucena-Frédou et al (2010) in Combu Island (PA) observed absolute fecundity ranging from 40 to 3,375 eggs/female, with a mean value of 905 ± 590 SD eggs/female. Da Silva et al (2004), found average values between 696 (females with 5.0 to 5.5 cm total length) and 1554 eggs/female (9.5 to 10.0 cm).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Santos (1978) defined fecundity as the number of eggs laid by one female per spawning. However, Bond & Buckup (1982) defined fecundity as the number of eggs per spawning that was found adhered to the female pleopods (Da Silva et al, 2004). When estimating the reproductive potential and future stock size of a given species or population, the fecundity is an important parameter (Mori et al, 1998;Hattori & Pinheiro, 2003).…”
Section: __________________mentioning
confidence: 99%
“…Freshwater decapod crustaceans are a group of high ecological and economic importance (Silva et al, 2004;Almeida et al, 2008). Shrimps and crabs play important ecological roles in streams, processing allochthonous matter by ingestion and bioturbation (March et al, 2001;Souza and Moulton, 2005).…”
Section: Introductionmentioning
confidence: 99%